197k views
3 votes
Transfer transfer the system of equations by forming a matrix equation.

2x - 3y = 19
x + 2y = -1
he multiplies the left side of the coefficient matrix by the inverse matrix.

how does he proceed to the solution?​

Transfer transfer the system of equations by forming a matrix equation. 2x - 3y = 19 x-example-1
User Stackular
by
4.9k points

1 Answer

6 votes

Answer:

Explanation:


\begin{bmatrix}2 & -3\\ 1 & 2\end{bmatrix}^(-1)* \begin{bmatrix}2 & -3\\ 1 & 2\end{bmatrix}* \begin{bmatrix}x\\y \end{bmatrix}=(1)/(7) \begin{bmatrix}2 & 3 \\ -1 & 2\end{bmatrix}* \begin{bmatrix}19\\ -1\end{bmatrix}

Since,
\begin{bmatrix}2 & -3\\ 1 & 2\end{bmatrix}^(-1)=(1)/(7)\begin{bmatrix}2 & 3\\ -1 & 2\end{bmatrix}

And
A^(-1)A=I


\begin{bmatrix}x\\y \end{bmatrix}=(1)/(7)\begin{bmatrix}2 & 3\\ -1 & 2\end{bmatrix}* \begin{bmatrix}19\\-1 \end{bmatrix}


\begin{bmatrix}x\\y \end{bmatrix}=(1)/(7)\begin{bmatrix}35\\ -21\end{bmatrix}


\begin{bmatrix}x\\y \end{bmatrix}=\begin{bmatrix}5\\ -3\end{bmatrix}

Therefore, x = 5 and y = -3 will be the value of variables.

User Lumbendil
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.